Management of paddy bunt (Tilletia barclayana) through mechanical seed processing - KUMAR, ASHWANI; GUPTA, ANUJA (The Indian Journal of Agricultural Sciences, 2023)
Paddy bunt or kernel smut of rice caused by Tilletia barclayana (Syn. Neovossia barclayana, N. horrida) is majordisease of rice growing countries. Seeds of two lots of Pusa 44 variety produced during kharif 2014 and one lotproduced during kharif 2015 were processed. Pre-cleaner and screen grader removed 44.7, 34.8 and 42.2% of totalbunt infected seed present in the three seed lots and reduced bunt infection from 1.32 to 0.73, 1.58 to 1.03 and 3.05 to1.76%, respectively. Eighteen combination treatments comprising of three deck slopes (S1- 2.50, S2- 2.00, S3- 1.50),three feedings (F1- 9 kg, F2- 12 kg, F3- 15 kg per minute) and two output settings (O1- 30cm deck width, O2- 40cmdeck width) of specific gravity separator were studied with an objective of getting maximum bunt free seed per unitof time. Maximum seed recovery (13.27 and 13.31 and 13.60 kg/minute) and bunt infection in final product (0.44,0.41 and 0.46%) with 89.1, 89.7 and 92.3% recovery efficiency was obtained by the treatment S3F3O2 (slope of deck1.50, feeding 15 kg/minute, output deck width 40 cm) in the three seed lots. Thus, mechanical processing reducedbunt infection by more than 65%, depending on the intensity of infection, as well as increased seed quality i.e. seedgermination improved by 6.5% and physical purity by 5.34%.